Pengaruh Media Sosial Whatsapp Terhadap Hasil Belajar Mata Pelajaran Ekonomi Siswa Kelas X SMAS Purnama Jakarta - Nuramalia, Ainun; Adawiyah, Robiatul; Taufik, Taufik (LITERATUS, 2024)
The aim of this research is to determine the influence of WhatsApp social media on learning outcomes in economics subjects. By using a quantitative approach method, the sampling technique in this research uses nonprobability sampling with a sampling technique using saturated sampling, where the number of samples is the same as the population. The number of samples used was 48 students. After conducting research according to the title "The Influence of WhatsApp Social Media on Learning Outcomes for Class X Economics Subjects at SMAS Purnama Jakarta". It can be concluded thatFrom the results of the analysis, it is obtained that the regression equation Y= 86.1703 – 0.1318 , meaning that for every 1% increase in use of WhatsApp social media, it will reduce learning outcomes in economics subjects by 0.1318. The correlation results of rxy = -0.175 indicate that there is a very low relationship between social media and learning outcomes. The Coefficient of Determination of 3.06% shows that WhatsApp social media contributes to learning outcomes by 3.06% while the remaining 96.94% is the contribution of other factors, such as physical, physiological and also family factors. This is also reinforced by the results obtained from hypothesis testing which show that it is smaller than 1.225 < 1.678 which states that there is a negative influence of WhatsApp social media on the learning outcomes of class X economics subjects at SMAS Purnama Jakarta.